STRATEGI CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM MENANAMKAN NILAI-NILAI MULTIKULTURAL PADA PEMBELAJARAN AGAMA ISLAM DI SMP NEGERI KECAMATAN GEDONG TATAAN PESAWARAN - Hadi, Fajrul; Syafei, Imam; Cahaya Kesuma, Guntur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to analyze the implementation of the Contextual Teaching and Learning (CTL) strategy in instilling multicultural values in Islamic Religious Education at public junior high schools (SMP Negeri) in Gedong Tataan District, Pesawaran. The research focuses on SMP Negeri 1 Pesawaran and SMP Negeri 26 Pesawaran, which exhibit a diverse background in terms of religion, ethnicity, and socio-economic status. The study employs a qualitative approach with data collection techniques including observation, interviews, and document analysis. The findings reveal that the implementation of the CTL strategy successfully enhances multicultural awareness among students, strengthens tolerance, and promotes active participation in the learning process. However, challenges such as limited time and insufficient teacher understanding of the CTL method were identified. The study recommends further training for teachers and the development of more contextually relevant teaching materials to support the effective implementation of CTL.